A return to sources: the folk life legacy of Eric R. Cregeen. (2nd July 2020) - Bennett, Margaret
ABSTRACT: Eric R. Cregeen (1921–83): was described in 2005 by the Historiographer Royal of Scotland as 'a social scientist of the highest order … a very fine historian and a very fine anthropologist … far in advance of this time … no one since has put the two disciplines together so effectively to illuminate the life of the Highlands.' (Professor T. C. Smout, University of St Andrew's). This paper gives a short biography of Cregeen's life and follows his career that earned him the highest acclaim among scholars of folklore, folklife and language, as well as social, economic and oral history. Benefitting from training from the Irish Folklore Commission, and fieldwork experience in the Manx Museum, he moved to Scotland in 1954. Cregeen devoted the rest of his life to documenting traditions of the West Highlands, leaving a legacy of recordings and journals which now provide a rich resource for further research.